Temporal effects of cutting intensity on Diptera assemblages in eastern Borneo rainforest Indonesia - ahmad - budiaman; Noor Farikhah Haneda; Indahwati -; Dini febrian; Laela Nur Rahmah (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Budiaman A, Haneda NF, Indahwati, Febrian D, Rahmah LN . 2020. Temporal effects of cutting intensity on Diptera assemblages in eastern Borneo rainforest Indonesia. Biodiversitas 21: 1074-1081. Studies on the effects of varying cutting intensity on the abundance and species richness of Diptera in tropical rainforest are limited, particularly in Southeast Asia region. The aim of the study was to assess the temporal effect of cutting intensity on Diptera community in tropical rainforest in the eastern Borneo rainforest, Indonesia, which was logged using the Indonesian Selective Cutting and Planting system. The field study was carried out in 2016. Responses of Diptera to the Indonesian Selective Cutting and Planting systems in the eastern Borneo rainforest, Indonesia were examined. We compared the abundance and morphospecies composition of Diptera before cutting and after cutting at three different treatments: low cutting intensity, medium cutting intensity and high cutting intensity. Diptera was collected using a malaise trap. Selective cutting of tropical rainforest altered biodiversity of Diptera. The abundance and morphospecies composition of Diptera were greater after cutting than before cutting at all cutting intensities. Our study showed that cutting intensity did not significantly affect the abundance and morphospecies composition of Diptera. Results of the study clearly indicated that the percentage of forest canopy cover could be a single predictor for abundance and morphospecies composition of Diptera in the natural rainforest of eastern Borneo, Indonesia.